THE FUNCTION OF IRONY IN THE WORKS OF JANE AUSTEN - Qosimova Saida Umidjon qizi; Abduramanova Diana Valerivna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This essay examines how irony functions in Jane Austen’s books, emphasising how it advances the plot, develops characters, and serves as a social critique. Austen’s approach is characterised by her use of irony, which allows her to expose the complexities of human nature and question social conventions. The essay emphasises how irony enhances the story and draws readers in with a deeper comprehension of the characters and issues in her writing